EVALUASI PELAKSANAAN PEMBELAJARAN DI MTs DARUL ULUM KOTABARU - Hartini Hartini; Radiatul Adawiah (STKIP Paris Barantai, 2018)
AbstractThis research aims at describing the evaluation result of Mathematic learning procces in MTs Darul Ulum Kotabaru as well as discovering the problems in Mathematics learning process in MTs Darul Ulum Kotabaru which consit of planning the lesson, presenting the lesson, and learning evaluation. The instrument used in this research were questionnaires, observasi sheets, and documentations. The subjects of this research were 2 mathemathics teachers who taught call VII and have joined 2013 curriculum training. The collected data were analyzed qualitatively The results of the research reveal that: (1) in terms Contex Evaluation, this aspect shows that there is suitability of school readiness, teachers, and objectives of Mathematics learning program in MTs Darul Ulum Kotabaru, it is categorized as very good, (2) in terms of Input Evaluation, on the input aspect in Mathematics learning, the subject of SM, NJ are in good category, (3) in terms of Process evaluation, on the process aspect, Mathematics learning process for subjects SM is in good category and subject NJ is on fair category, and (4) in terms of Product Evaluation, Mathematics learning assessment of the teachers based on 2013 curiculum on subject SM and NJ who have joined 2013 curiculum training is in fair category. Keyword: Mathematics learning, evaluation, 2013 curiculum